LEARNING TIME MANAGEMENT, LEARNING ENVIRONMENT IN-HOME AND LEARNING MOTIVATION WITH MATHEMATICS LEARNING OUTCOMES - Chaerunnisah Chaerunnisah; Suparyan Suparyan (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
Poor student learning outcomes are associated with many factors. The relationship between learning time management, learning environment in the home, and learning motivation are possible related to learning outcomes. This research aims to determine the presence or absence of positive and significance the relationship between learning time management, learning environment in-home, and learning motivation with Mathematics Learning Outcomes in Students Class X Motorcycle Engineering (TSM) of State Vocational High School (SMK Negeri)) 1 Pleret Bantul Regency in even semester in the academic year of 2016/2017. This research population was the students of X TSM grade in SMK Negeri 1 Pleret Bantul Regency in 2016/2017, consisting of class X TSM A and X TSM B, totaling 66 students. Samples were taken from X TSM A as the research sample class and with the random sampling technique. The writer uses the questionnaire method to collect the data of learning independence, parent's attention, and student's interaction with teacher and test method to get the resulting learning of math. The research instrument: validity test, different power test, and reliability test. Test requirement analysis includes a test of normality, a test of linearity, and independence. The writer uses product-moment correlation analysis and multiple linear regression analysis to analyze the data. The results showed a positive and significant relationship between learning time management, learning environment in the home, and learning motivation with mathematics learning outcomes in students class X TSM in even Semester of SMK Negeri 1 Pleret Bantul Regency in the academic year of 2016/2017. It is showed by Fcount > Ftable is 6,8465 >2,92 with R = 0,6375 and R2 = 0,4064 with Y Ì‚=(201,9710)+0,3909 X_1+0,3076 X_2+0,8385 X_3, with RCã€– Xã€—_1=23,9976 %, RCã€– Xã€—_2=20,1644 % and RC X_3=55,8380 %, EC X_1=9,7528%, EC X_2=8,1949% and EC X_3=22,6929%.